Peningkatan Efikasi Diri Pasien Diabetes Militus Pada Masa Pandemi - Brigitta Ayu Dwi Susanti; Amanda Marselin (Poltekkes Kemenkes Kupang, 2021)
Background: In Indonesia, the prevalence of non-communicable diseases has increased from year to year, one of which is diabetes mellitus (DM). Based on the 2018 Basic Health Research (RISKESDAS), one of the PTM whose prevalence has increased significantly is diabetes mellitus, namely in 2013 as much as 6.9% and 2018 increasing to 8.5%, DIY ranks third highest in Indonesia. Today's modern lifestyle is one of the reasons for the increasing prevalence of DM. Most DM sufferers are not aware of the symptoms of DM disease they are suffering from, so they will only consult a doctor after complications such as neuropathy, diabetic ulcers, nephropathy and others appear. DM patient compliance in various aspects, ranging from routinely taking drugs, exercise, diet, monitoring blood sugar levels, and others is very important in the management of DM therapy. This is sometimes still not getting attention because in terms of self-efficacy because DM is a chronic disease that requires a long period of treatment even for life. Research method: quasi-experimental pre and post test with 20 respondents with DMSES (The Diabetes Management Self Efficacy Scale). Results: there was an increase in self-efficacy in DM patients during the pandemic by providing educational leaflets and videos p<00.5 with the Wilcoxon test. Therefore, during a pandemic, the right method is needed to increase self-efficacy in Diabetes Mellitus patients, one of which is through leaflets and educational videos.